Study of ideal topical pharyngeal anesthesia in upper gastrointestinal system endoscopy: A double-blind, randomized, controlled trial - Çam, Hakan; Pehlivan, Seda; Dağ, Muhammed Sait; Yılmaz, Nimet; Demir, Umut; Gülşen, Murat Taner (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: This study is designed to determine which drug forms provide ideal pharyngeal anesthesia when used during upper gastrointestinal system endoscopy. Materials and Methods: A total of 180 patients were included in the study. Using the random number table, these patients were divided into three groups. Group 1, lidocaine gel+isotonic spray; Group 2, base lubricant gel+lidocaine spray; and Group 3: lidocaine gel+lidocaine spray. Data were collected from the patient identification form, compliance to operation form, and State Anxiety Inventory. Results: Anesthetization and compliance to procedure scores were higher and anxiety scores were lower in Group 3 than in other groups (p<0.05). It was observed that as the compliance score increased, the anesthetization and satisfaction scores also increased; however, coughing during the procedure, duration of the procedure, and anxiety scores decreased (p<0.05). It was determined that as anesthetization scores increased, discomfort in the throat caused by the device, coughing during the procedure, and anxiety scores decreased (p<0.05). Conclusion: Lidocaine gel and spray combination is the most ideal pharyngeal anesthesia to ensure the adaptation of the patient to the procedure and to decrease anxiety and discomfort during the procedure.